Pengaruh Dewan Komisaris dan Kepemilikan Manajerial terhadap Kinerja Keuangan pada Sub Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Aufadillah Aufadillah; Aminar Sutra Dewi (ARZUSIN, 2026)
The food and beverage industry listed on the Indonesia Stock Exchange (IDX) faces challenges in maintaining optimal financial performance amid intense market competition. In this context, the Board of Commissioners and Managerial Ownership play an important role in supervising and managing company resources. This study aims to analyze the effect of the Board of Commissioners and Managerial Ownership on company financial performance in the food and beverage industry subsector listed on the IDX for the 2019–2023 period. This study used a quantitative approach with a descriptive research design. The research sample consisted of 18 companies selected using purposive sampling, while data were collected from annual reports published by the IDX. Data were analyzed using panel data regression with the assistance of EViews. The results showed that the Board of Commissioners had a positive and significant effect on company financial performance as measured using Return on Assets (ROA). Conversely, Managerial Ownership did not show a significant effect on company financial performance. These findings contribute to the development of corporate governance studies and expand understanding of the role of corporate governance mechanisms in improving financial performance. The implications of this study provide insights for investors and company managers regarding the importance of strengthening the supervisory function of the Board of Commissioners and the efficiency of company management in the food and beverage subsector.